Kebijakan Lindung Nilai (Hedging) pada Perusahaan untuk Menjamin Kinerja Perusahaan - Muftiasa, Afdol; Wibowo, Lili Adi; Hurriyati, Ratih; Rahayu, Agus (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
Risk fluctuations, including such changes in interest rates, exchange rates, and commodity prices, have a negative impact on business performance and can be mitigated by hedging. Derivative instruments are the preferred method for hedging. Internal hedging calculations take into account size, growth prospects, financial distress, leverage, and liquidity. This study's goal is to examine the variables that influence the hedging decisions of businesses. This study employs a descriptive qualitative methodology. The most influential factors in determining a company's hedging strategy are its size and growth prospects, according to the research. The greatest effect comes from the company's size and growth potential in order to influence the company's hedging policies. Other factors such as leverage, liquidity, financial distress, market depth risk are not so dominant in influencing the company's hedging decisions. However, several variables or factors that are not the dominant factor will be important according to the industry or line of business of each company.Recommendations for further research can be carried out by analyzing the company's external factors that influence hedging decisions.